1993
DOI: 10.1089/dna.1993.12.283
|View full text |Cite
|
Sign up to set email alerts
|

HNF1 Activates Transcription of the Human Gene for Insulin-Like Growth Factor Binding Protein-1

Abstract: Insulin-like growth factor binding protein-1 (IGFBP-1) is expressed primarily in the liver, kidney, and uterus. Basal IGFBP-1 promoter activity in human HEP G2 hepatoma cells is dependent upon a proximal promoter element that binds hepatic nuclear factor 1 (HNF1), a protein that is likely to be an important factor regulating the expression of many genes in liver and kidney. To test whether HNF1 activates IGFBP-1 transcription, HEP G2 cells and HeLa cells were cotransfected transiently with HNF1 expression vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 40 publications
5
80
1
1
Order By: Relevance
“…LID mice demonstrated a sixfold reduction in serum levels of IGFBP-1 and IGFBP-3. Insulin levels are inversely related to those of IGFBP-1, as it has been shown that insulin directly inhibits the production of IGFBP-1 in human hepatoma cell lines (39,40). It is therefore likely that the high levels of circulating insulin in LID mice may have caused the reduction in IGFBP-1 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LID mice demonstrated a sixfold reduction in serum levels of IGFBP-1 and IGFBP-3. Insulin levels are inversely related to those of IGFBP-1, as it has been shown that insulin directly inhibits the production of IGFBP-1 in human hepatoma cell lines (39,40). It is therefore likely that the high levels of circulating insulin in LID mice may have caused the reduction in IGFBP-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, it has been argued that IGFs were unlikely to have any direct metabolic role, particularly with respect to glucose homeostasis. However, more recent data indicate that circulating IGF-I and its binding proteins, particularly IGFBP-1, are capable of modulating glucose levels and may have direct effects on glucose homeostasis (14,39,40). Clinical studies performed on normal subjects as well as patients with type 1 and type 2 diabetes (44,46 -49) showed that IGF-I enhances insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known thatc irculatingI GFBP-1, due to its inverser elationship with insulin, becomes suppressed afteri ntake of meals and glucose (30)(31)(32)(33)(34).F or this reason, serumI GFBP-1 hasb eene mployeda sa n estimate of b -cellf unction and insulin sensitivity in numerous clinical conditions, including liverc irrhosis (19,35).Inthe present study,baseline levels of IGFBP-1 were elevated moret hant wofoldi np atientsw ith cirrhosis as compared to healthys ubjects, in keeping with the cirrhosis-related insulin resistance (19,25). Nevertheless, following the 75 gg lucose load (90-180 min),c irrhotic patients showed the same relative suppression of IGFBP-1( 21-32%) as that observed in healthycontrols( 19-41%), while IGFBP-2 remained unchanged during the OGTT in both study groups.T hus,d espite ther educedh epatic insulin sensitivity resulting in higherb aseline levels,t he hepatocytes were able to respond 'normally' to an increased insulin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other IGFBPs, circulating IGFBP-1 changes rapidly and shows diurnal rhythms according to food intake. This is because insulin is the predominant inhibitor of IGFBP-1 transcription (Orlowski et al 1991, Powell et al 1991. Circulating IGFBP-1 and insulin levels therefore show an inverse relationship.…”
Section: Introductionmentioning
confidence: 99%